BARACK OBAMA’S VICTORY SPEECHES THROUGH ILLOCUTIONARY ACT (Universitas Muhammadiyah Palembang, 2022)
This research deals with the analysis of illocutionary act found in Barack Obama’s victory speeches. The purpose of this research was to analyze the illocutionary act which produced by Barack Obama in his victory speeches.This research used descriptive qualitative method where the researcher analyzed one by one the type of illocutionary act which produced by Barack Obama in his victory speeches. The researcher used the theory from Alston for illocutionary act. From the research, the researcher found that there were 31 statements of illocutionary act produced by Barack Obama in his victory speeches. They were 20 statements for expressive, 7 statements of directives and 4 statements of comissive. The researcher did not find any excertive in Barack Obama’s victory speeches. The result showed that the most dominant type of illocutionary act found in Barack Obama’s victory speeches was expressive.